Pengaruh Pengaruh Kegiatan Market Day Terhadap Nilai-nilai Kewirausahaan - Yamasyani Brasehlla; Laily Rosidah; Fahmi Fahmi (Jurnal Kajian Anak (J-Sanak), 2023)
Early childhood is a period of growth, development, and processing for individuals. During this golden period, educational support is required to provide stimulation so that every child's potential can be developed. Therefore, activities that can facilitate every child's potential are implemented in early childhood education, such as through market day activities. Through market day activities, entrepreneurial values can be instilled from an early age. This study aims to analyze the effect of market day activities on entrepreneurial values in 5-6 year old children at the Kindergarten in Cipare, Serang, Banten. Hence, this study employs a quantitative approach with an ex post facto method, and the sample type is purposive sampling of 70 children aged 5-6 years. The instrument used in this study is a questionnaire utilizing the likert scale assessment technique and documentation. Based on the results obtained in this study, the simple linear regression significance value 0.000, and the correlation value (R) 0.646, indicating that Hı is accepted, and Ho is rejected. Therefore, the data is stated to have a positive influence of 64.6% between market day activities and entrepreneurial values in early childhood in Cipare, Serang, Banten. Keywords: Quantitative, Market Day, Entrepreneurial Values